2021
DOI: 10.1177/07419325211054208
|View full text |Cite
|
Sign up to set email alerts
|

Data Literacy Training for K–12 Teachers: A Meta-Analysis of the Effects on Teacher Outcomes

Abstract: This meta-analysis explores training teachers in the use of data, defined as any quantifiable information that helps teachers know more about their students for instructional decision-making. The questions addressed are as follows: (a) What are the features of data literacy training for kindergarten through 12th-grade teachers? (b) What are the effects of data literacy training on kindergarten through 12th-grade teacher outcomes? and (c) Do training characteristics moderate the effects of training? A comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Although TDL offers a powerful information literacy framework, teachers may struggle to implement it in the classroom (Pierce et al, 2014 ; Gelderblom et al, 2016 ; Filderman et al, 2021 ; Xin, 2021 ). Moreover, TDL has largely been excluded from accounts of teachers' knowledge development (Reeves and Chiang, 2018 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TDL offers a powerful information literacy framework, teachers may struggle to implement it in the classroom (Pierce et al, 2014 ; Gelderblom et al, 2016 ; Filderman et al, 2021 ; Xin, 2021 ). Moreover, TDL has largely been excluded from accounts of teachers' knowledge development (Reeves and Chiang, 2018 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research has identified significant gaps in teacher data literacy (TDL). For instance, most of the teachers in Filderman et al's ( 2021 ) study displayed difficulties in locating, comprehending, and interpreting data. While teachers have long worked with data, their roles have traditionally positioned them more passively as evaluators and implementers of educational interventions (Xin, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge is a component of data consciousness (Filderman et al, 2022 ), and data consciousness is the cornerstone of cultivating teachers' precision teaching ability. Therefore, this paper argues that data consciousness plays a mediating role between internal and external knowledge transformation and teachers' precision teaching ability.…”
Section: Literature Review and Theoretical Assumptionsmentioning
confidence: 99%
“…Collaboration is particularly important for teachers’ data literacy (Jimerson & Wayman, 2012) and their ongoing use of data (Means et al, 2011; Piro et al, 2014). In a recent meta-analysis, Filderman et al (2021) reported that training improved teachers’ data literacy, and further, training with a collaborative component was associated with larger effects on knowledge and skills. These findings were consistent with prior research observing that teachers in small groups interpret data more accurately, clarify problems, ask follow-up questions, problem-solve, and correct errors (Means et al, 2011).…”
Section: Collaboration and Data Usementioning
confidence: 99%